A Slacks-Based Measure Approach for Efficiency Measurement of Recycling Production Systems with Imprecise Data - Huang-Chu Huang; Fung-Bao Liu; Cheng-Feng Hu (Journal of Mathematics)
Resource scarcity and environmental degradation have made sustainable resource utilization and environmental protection worldwide. The development of the circular economy is considered an approach for more appropriate economic and environmental management. In this work, a slack-based measure approach was proposed for the assessment of recycling production systems with imprecise data. The two-level mathematical programming approach was employed for obtaining the lower and upper bounds of fuzzy efficiencies by transformed conventional single-level mathematical programs. The relationship between the fuzzy system efficiency and process efficiencies was explored. The proposed method was applied to assess the recycling production system of EU countries. Our results show that the performance of the production system in EU countries was superior to that of the recycling system, and the inefficiency of the whole system was attributed mainly to the recycling inefficiency.